The collected poems of A.E. Housman - Housman, A.E (New york: Holt, 2012)
This collection contains 2 collections of poems from A.E. Housman--a Shropshire Lad and Last Poems, totaling 104 poems! It includes an active Table of Contents and has been formatted for smooth navigation and optimal viewing on the Kindle!
Keywords: LITERATURA; POEMARIO